2019
DOI: 10.26434/chemrxiv.8060000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating Polymer Representations via Quantifying Structure-Property Relationships

Abstract: Machine learning techniques are being applied in quantifying structure-property relationships for a wide variety of materials, where the properly representing materials plays key roles. Although algorithms for representation learning are extensively studied, their applications to domain-specific areas, such as polymer, are limited largely due to the lack of benchmark databases. In this work, we investigate different types of polymer representations, including Morgan Fingerprint (MF), molecular embedding (ME) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Their performances are generally slightly worse than the previous two groups of models. A R 2 around 0.85 and an MAE around 30 using two-monomer structure representation were reported in the literature for T g prediction, 43 which is at the same level as our single monomer-based models. Only through the evaluation on Data set_2, it is realized that the model has a relatively poor generalization ability.…”
Section: Repeatunit As Polymer'ssupporting
confidence: 83%
See 2 more Smart Citations
“…Their performances are generally slightly worse than the previous two groups of models. A R 2 around 0.85 and an MAE around 30 using two-monomer structure representation were reported in the literature for T g prediction, 43 which is at the same level as our single monomer-based models. Only through the evaluation on Data set_2, it is realized that the model has a relatively poor generalization ability.…”
Section: Repeatunit As Polymer'ssupporting
confidence: 83%
“…Monomers, repeat units, and oligomers corresponding to several repeat units chained together are representatives of long-chain polymers. 11,16,43 Compared to monomers, the repeat unit contains bonding information indicated by the "*" symbol in their SMILES representation, which explicitly suggests the polymerization point of a polymer. Chaining several repeat units together incorporates more structure information in the originally long-chain polymer, but whether an oligomer is better than a monomer or a repeat unit remains ambiguous.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides ML models, recent findings showed that properly representing polymer molecules can be important for constructing accurate surrogate models, since representations describe the chemistry of molecules. 249 It was found that a deep learning representation scheme (i.e., Mol2Vec) based on the Natural Language Process (NLP) algorithm was better than the conventionally used Morgan Fingerprint, a one-hot encoding scheme based on the simple chemical connections. Even if a chemistry-thermal conductivity relation can be identified from ML, properly including processing conditions as descriptors could be another obstacle for eventually validate the model prediction, as processing conditions can impact the morpology which in turn influence thermal conductivity.…”
Section: Data-driven Explorationmentioning
confidence: 99%
“…Researchers have made active and effective attempts to apply ML method in exploring polymer syntheses and polymer materials [22]. The copolymer synthesis and defectivity [23,24,25], mechanical properties of polymer composites [26], liquid crystal behavior of copolyether [27], thermal conductivity [28], dielectric properties [29], glass transition, melting, and degradation temperature and quantum physical and chemical properties [30,31,32,33] have been applied with machine learning and good prediction accuracy is achieved. Muramatsu et al [34] have used ML method to investigate the relationship between the phase separation structure of polymer blend and Young's modulus, and builds a predictive framework based on two-dimensional images of polymer blend as the descriptor.…”
Section: Introductionmentioning
confidence: 99%